Simulation of secondary emission calorimeter for future colliders - Yetkin, E. A.; Yetkin, T.; Ozok, Ferhat; Iren, E.; Erduran, Mustafa Nizamettin; Erduran, Mustafa Nizamettin (IOP Publishing LTD, 2017)
We present updated results from a simulation study of a conceptual sampling electromagnetic calorimeter based on secondary electron emission process. We implemented the secondary electron emission process in Geant4 as a user physics list and produced the energy spectrum and yield of secondary electrons. The energy resolution of the SEE calorimeter was sigma/E = (41%) GeV1/2/root E and the response linearity to electromagnetic showers was to within 1.5%. The simulation results were also compared with a traditional scintillator calorimeter.
Conference on Calorimetry for the High Energy Frontier (CHEF) -- OCT 02-06, 2017 -- Lyon, FRANCE
WOS: 000427226600003
Keywords: Calorimeter methods; Detector modelling and simulations II (electric fields charge transport multiplication and induction pulse formation electron emission etc); Electron multipliers (vacuum)